Agama, Persoalan Sosial, dan Krisis Moral - Syamsul Bakri (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2009)
As a part of social system, Islam is a powerful and huge potential to build our country. Therefore, Islam must playas inclusive, democratic, and plurals power. Islamic thought characteristic must have socio-cultural movement paradigm bytrying to show Islam’s form in daily life consciousness and build social institution system without religion banner. Socio-culturalmovement inclines to awareness and empowerment act to society and its institution as its commitment to democracy anddevelopment of autonomous civil society. When Islamic thought function as this cultural power, sociologically Islam willappear as social salvation. Therefore, this religion will be more down to earth and relevant to socio-historic problem at daily life.Islam will have role to liberate human from poverty, human rights violation, backwardness, corruption, etc